Reliability assessment of an isolated hybrid microgrid using Markov modeling and Monte Carlo simulation - Saleem, Ahmad F. (Array, 2021)
The importance of conducting adequacy assessments of standalone systems with integrated renewable generation sources is growing. In this work, the focus is placed on the reliability assessment of an isolated microgrid operating on renewable energy generated by wind turbines (WTs) and photovoltaic (PV) panels. Batteries for storage were included in the model because of their crucial role in the system"s feasibility. Additional micro-gas turbines (MGTs) served as conventional backup. The sequential Monte Carlo simulation (SMCS) method was used to carry out simulations of the system, which was modeled using Markov matrices. Input data, such as wind speed, solar irradiance, and ambient air temperature, were used to simulate the power outputs of the generators. These historical data were fitted into appropriate distributions to extract corresponding parameters when simulating essential key factors necessary to produce the renewable power generation models. The adequacy model of the MGTs was obtained by employing the two-state reliability model, which was also superimposed with the generation models of WTs, PV panels, and batteries. The IEEE Roy Billinton test system (RBTS) was used for demand modelling. Common reliability indices were computed, and the system availability margins were evaluated.